REVERBERATION RESPONSES IN LIGHT CURVES OF THE Q2237+0305 QUASAR - Berdina, L. A.; Tsvetkova, V. S.; Shulga, V. M. (Видавничий дім «Академперіодика», 2018)
PACS number: 98.54.AjPurpose: Studying the spatial structure of the quasar in the Q2237+0305 gravitational lens system in optical spectral range; estimating the central black hole mass.Design/methodology/approach: The method of reverberation mapping has been used that implies measuring of the time delays between the quasar intrinsic brightness variations in different spectral ranges. We used the macroimage light curves of the Q2237+0305 system in spectral bands V (λeff = 547.7 nm) and R (λeff = 634.9 nm) of Johnson–Cousins photometric system. The reverberation mapping method allows to obtain direct estimates of distances between the quasar regions responsible for radiation in the selected spectral bands.Findings: The time delay between the V and R light curves is estimated to be 5.58±1.69 days, which is more than an order of magnitude larger than that predicted by a standard thin accretion disk model by Shakura–Sunyaev. As an explanation, a suggestion is made that the standard accretion disk model is not entirely adequate when describing an actual quasar structure.Conclusions: Such a large time delay means that reverberation responses arise in extended structures located outside the accretion disk. A suggestion that some extended structure capable to efficiently radiate in optical band may exist around the accretion disks has been reported in a number of works dedicated to the microlensing studies and analysis of flux ratio anomalies in gravitationally lensed quasars. Abolmasov and Shakura have shown analytically that a super-Eddington accretion regime may take place for some quasars, which leads to formation of an envelope. The envelope scatters radiation from the disk, thus making the apparent disk size larger. The further development in studying the spatial structure of the Q2237+0305 quasar with the use of reverberation mapping implies involving the data in spectral band I. This will provide two additional  spectral bases thus allowing investigation of a wavelength dependence of the corresponding structure dimensions.Key words: quasar, black hole, spatial structure, accretion disk, reverberation mappingManuscript submitted  19.10.2018Radio phys. radio astron. 2018, 23(4): 235-243REFERENCES1. SHAKURA, N. I. and SUNYAEV, R. A., 1973. Black holes in binary systems. Observational appearance. Astron. Astrophys. vol. 24, pp. 337–355.2. KROLIK, J. H., HORNE, K., KALLMAN, T. R., MALKAN, M. A., EDELSON, R. A. and KRISS, G. A., 1991. Ultraviolet variability of NGC 5548 – Dynamics of the continuum production region and geometry of the broadline region. Astrophys. J. vol. 371, is. 2, pp. 541–562. DOI:https://doi.org/10.1086/1699183. BLANDFORD, R. D. and MCKEE, C. F., 1982. Reverberation mapping of the emission line regions of Seyfert galaxies and quasars. Astrophys. J. vol. 255, pp. 419–439. DOI: https://doi.org/10.1086/1598434. EDRI, H., RAFTER, S. E., CHELOUCHE, D., KASPI, SH. and BEHAR, E., 2012. Broadband Photometric Reverberation Mapping of NGC 4395.  Astrophys. J. vol. 756, is. 1, id. 73. DOI: https://doi.org/10.1088/0004-637X/756/1/735. BACHEV, R. S., 2009. Quasar optical variability: searching for interband time delays. Astron. Astrophys. vol. 493, is. 3, pp. 907–911. DOI: https://doi.org/10.1051/0004-6361:2008109936. WANDERS, I., PETERSON, B. M., ALLOIN, D., AYRES, T. R., CLAVEL, J., CRENSHAW, D. M., HORNE, K., KRISS, G. A., KROLIK, J. H., MALKAN, M. A., NETZER, H., O’BRIEN, P. T., REICHERT, G. A., RODRÍGUEZ-PASCUAL, P. M., WAMSTEKER, W., ALEXANDE, T., ANDERSON, K. S. J., BENITEZ, E., BOCHKAREV, N. G., BURENKOV, A. N., CHENG, F.-Z., COLLIER, S. J., COMASTRI, A., DIETRICH, M., DULTZIN-HACYAN, D., ESPEY, B. R., FILIPPENKO, A. V., GASKEL, C. M., GEORGE, I. M., GOAD, M. R., HO, L. C., KASPI, S., KOLLATSCHNY, W., KORIST, A. K. T., LAOR, A., MACALPINE, G. M., MIGNOLI, M., MORRIS, S. L., NANDRA, K., PENTON, S., POGGE, R. W., PTAK, R. L., RODRÍGUEZESPINOZA, J. M., SANTOS-LLEÓ, M., SHAPOVALOVA, A. I., SHULL, J. M., SNEDDEN, S. A., SPARKE, L. S., STIRPE, G. M., SUN, W.-H., TURNER, T. J., ULRICH, M.-H., WANG, T.-G., WEI, C., WELSH, W. F., XUE, S.-J. and ZOU, Z.-L., 1997. Steps toward Determination of the Size and Structure of the Broad-Line Region in Active Galactic Nuclei. XI. Intensive Monitoring of the Ultraviolet Spectrum of NGC 7469. Astrophys. J. Suppl. Ser. vol. 113, is. 1, pp. 69–88.7. COLLIER, S., HORNE, K., WANDERS, I. and PETERSON, B. M., 1999. A new direct method for measuring the Hubble constant from reverberating accretion discs in active galaxies. Mon. Not. R. Astron. Soc. vol. 302, is. 1, pp. L24–L28. DOI: https://doi.org/10.1046/j.1365-8711.1999.02250.x8. COLLIER, S., 2001. Evidence for accretion disc reprocessing in QSO 0957+561. Mon. Not. R. Astron. Soc. vol. 325, is. 4, pp. 1527–1532. DOI: https://doi.org/10.1046/j.1365-8711.2001.04568.x9. SERGEEV, S. G., DOROSHENKO, V. T., GOLUBINSKIY, YU. V., MERKULOVA, N. I. and SERGEEVA, E. A., 2005. Lag-luminosity relationship for interband lag between variations in b, v, r, and i bands in active galactic nuclei. Astrophys. J. vol. 622, is. 1, pp. 129–135. DOI: https://doi.org/10.1086/42782010. CACKETT, E. M., HORNE, K. and WINKLER, H., 2007. Testing thermal reprocessing in active galactic nuclei accretion discs. Mon. Not. R. Astron. Soc. vol. 380, is. 2, pp. 669–682. DOI: https://doi.org/10.1111/j.1365-2966.2007.12098.x11. FAUSNAUGH, M. M., STARKEY, D. A., HORNE, K., KOCHANEK, C. S., PETERSON, B. M., BENTZ, M. C., DENNEY, K. D., GRIER, C. J., GRUPE, D., POGGE, R. W., DE ROSA, G., ADAMS, S. M., BARTH, A. J., BEATTY, T. G., BHATTACHARJEE, A., BORMAN, G. A., BOROSON, T. A., BOTTORFF, M. C., BROWN, J. E., BROWN, J. S., BROTHERTON, M. S., COKER, C. T., CRAWFORD, S. M., CROXALL, K. V., EFTEKHARZADEH, S., ERACLEOUS, M., JONER, M. D., HENDERSON, C. B., HOLOIEN, T. W.-S., HUTCHISON, T., KASPI, S., KIM, S., KING, A. L., LI, M., LOCHHAAS, C., MA, Z., MACINNIS, F., MANNE-NICHOLAS, E. R., MASON, M., MONTUORI, C., MOSQUERA, A., MUDD, D., MUSSO, R., NAZAROV, S. V., NGUYEN, M. L., OKHMAT, D. N., ONKEN, C. A., OUYANG, B., PANCOAST, A., PEI, L., PENNY, M. T., POLESKI, R., RAFTER, S., ROMERO-COLMENERO, E., RUNNOE, J., SAND, D. J., SCHIMOIA, J. S., SERGEEV, S. G., SHAPPEE, B. J., SIMONIAN, G. V., SOMERS, G., SPENCER, M., STEVENS, D. J., TAYAR, J., TREU, T., VALENTI, S., VAN SADERS, J., VILLANUEVA JR, S., VILLFORTH, C., WEISS, Y., WINKLER, H. and ZHU, W., 2018. Continuum Reverberation Mapping of the Accretion Disks in Two Seyfert 1 Galaxies. Astrophys. J. vol. 854, is. 2, id. 107. DOI: https://doi.org/10.3847/1538-4357/aaaa2b12. GRIER, C. and SDSS-RM Collaboration, 2017. The Sloan Digital Sky Survey Reverberation Mapping Project: Quasar Reverberation Mapping Studies. American Astronomical Society Meeting. vol. 229, id. 414.01.13. KOPTELOVA, E. A., OKNYANSKIJ, V. L. and SHIMANOVSKAYA, E. V., 2006. Determining time delay in the gravitationally lensed system QSO2237+0305. Astron. Astrophys. vol. 452, is. 1, pp. 37–46. DOI: https://doi.org/10.1051/0004-6361:2005405014. KOPTELOVA, E., OKNYANSKIJ, V., ARTAMONOV, B., and CHEN, W.-P., 2010. Multiwavelengths observations of lensed quasars: interband time delays. Mem. S. A. It. vol. 81, pp. 138–143.15. DUDINOV, V. N., SMIRNOV, G. V., VAKULIK, V. G., SERGEEV, A. V. and KOCHETOV, A. E., 2010. Gravitational Lensed System Q2237-0305 in 2001–2008: Observations at the Maidanak Mountain. Radio Phys. RadioAstron. vol. 15, is. 4, pp. 387–398. (in Russian).16. TSVETKOVA, V. S., SHULGA, V. M. and BERDINA, L. A., 2016. A simple method to determine time delays in the presence of microlensing: application to HE 0435-1112 and PG 1115+080. Mon. Not. R. Astron. Soc. vol. 461, is. 4, pp. 3714–3723. DOI: https://doi.org/10.1093/mnras/stw154017. FRANK, J., KING, A. and RAINE, D. J., 2002. Accretion Power in Astrophysics. Third Edition. Cambridge: Cambridge University Press. https://doi.org/10.1017/CBO978113916424518. POINDEXTER, S. and KOCHANEK, C. S., 2010. Microlensing Evidence that a Type 1 Quasar is Viewed Face-On. Astrophys. J. vol. 712, is. 1, pp. 668–673. DOI: https://doi.org/10.1088/0004-637X/712/1/66819. AGOL, E., JONES, B. and BLAES, O., 2000. Keck Mid-Infrared Imaging of QSO 2237+0305. Astrophys. J. vol. 545, is. 2, pp. 657–663. DOI: https://doi.org/10.1086/31784720. MORGAN, C. W., KOCHANEK, C. S., MORGAN, N. D. and FALCO, E. E., 2010. The Quasar Accretion Disk Size-Black Hole Mass Relation. Astrophys. J. vol. 712, is. 2, pp. 1129–1136. DOI: https://doi.org/10.1088/0004-637X/712/2/112921. AGOL, E. and KROLIK, J. H., 2000. Magnetic Stress at the Marginally Stable Orbit: Altered Disk Structure, Radiation, and Black Hole Spin Evolution. Astrophys. J. vol. 528, is. 1, pp. 161–170. DOI: 10.1086/3081722. GASKELL, C. M., GOOSMANN, R. W. and KLIMEK, E. S., 2008. Structure and kinematics of the broadline region and torus of Active Galactic Nuclei. Mem. S. A. It. vol. 79, pp. 1090–1095.23. EIGENBROD, A., COURBIN, F., MEYLAN, G., AGOL, E., ANGUITA, T., SCHMIDT, R. W. and WAMBSGANSS, J., 2008. Microlensing variability in the gravitationally lensed quasar QSO 2237+0305 = the Einstein Cross. II. Energy profile of the accretion disk. Astron. Astrophys. vol. 490, is. 3, pp. 933–943. DOI: https://doi.org/10.1051/0004-6361:20081072924. VIVES-ARIAS, H., MUÑOZ, J. A., KOCHANEK, C. S., MEDIAVILLA, E. and JIMÉNEZ-VICENTE, J., 2016. Observations of the Lensed Quasar Q2237+0305 with CanariCam at GTC. Astrophys. J. vol. 831, is. 1, id. 43. DOI: https://doi.org/10.3847/0004-637X/831/1/4325. ELVIS, M., 2000. A Structure for Quasars. Astrophys. J. vol. 545, is. 1, pp. 63–76. DOI: https://doi.org/10.1086/31777826. URRY, C. M. and PADOVANI, P., 1995. Unified Schemes for Radio-Loud Active Galactic Nuclei. Publ. Astron. Soc. Pac. vol. 107, no. 715, pp. 803–845. DOI:https://doi.org/10.1086/13363027. JAROSZYNSKI, M., WAMBSGANSS, J., and PACZYNSKI, B., 1992. Microlensed light curves for thin accretion disks around Schwarzschild and Kerr black holes. Astrophys. J. vol. 396, is. 2, pp. L65–L68. DOI: https://doi.org/10.1086/18651828. WITT, H. J. and MAO, S., 1994. Interpretation of microlensing events in Q2237+0305. Astrophys. J. vol. 429, is. 1, pp. 66–76. DOI: https://doi.org/10.1086/17430229. VAKULIK, V. G., SCHILD, R. E., SMIRNOV, G. V., DUDINOV, V. N. and TSVETKOVA, V. S., 2007. Q2237+0305 source structure and dimensions from light-curve simulation. Mon. Not. R. Astron. Soc. vol. 382, is. 2, pp. 819–825. DOI: https://doi.org/10.1111/j.1365-2966.2007.12422.x30. POOLEY, D., BLACKBURNE, J. A., RAPPAPORT, S. and SCHECHTER, P. L., 2007. X-ray and optical flux ratio anomalies in quadruply lensed quasars. I. Zooming in on quasar emission regions. Astrophys. J. vol. 661, is. 1, pp. 19–29.31. POINDEXTER, S., MORGAN, N. and KOCHANEK, C. S., 2008. The Spatial Structure of an Accretion Disk. Astrophys. J. vol. 673, is. 1, pp. 34–38. DOI: https://doi.org/10.1086/52419032. ABOLMASOV, P. and SHAKURA, N. I., 2012. Microlensing evidence for super-Eddington disc accretion in quasars. Mon. Not. R. Astron. Soc. vol. 427, is. 3, pp. 1867–1876. DOI: https://doi.org/10.1111/j.1365-2966.2012.21881.x33. OHSUGA, K. and MINESHIGE, S., 2011. Global Structure of Three Distinct Accretion Flows and Outflows around Black Holes from Two-dimensional Radiation-magnetohydrodynamic Simulations. Astrophys. J. vol. 736, is. 1, id. 2. DOI: https://doi.org/10.1088/0004-637X/736/1/2